1979
DOI: 10.1252/jcej.12.19
|View full text |Cite
|
Sign up to set email alerts
|

Extraction kinetics of copper with benzoylacetone during drop formation.

Abstract: The extraction rate of copper with benzoylacetone was studied by a single-drop method, as basic research on extraction kinetics of metals by chelating agents. Specifically, a study of the extraction rate during drop formation was carried out. A theoretical analysis of extraction kinetics accompanied by chemical reaction in the continuous phase was carried out for an (w, «)-th order reaction. The relationships between the extent of extraction during drop formation and drop formation time, concentrations of reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Their prolific contributions to the subject cover the extraction kinetics of copper with benzoylacetone during drop formation (199), during drop rise (200), in a stirred transfer cell (201), and with liquid surfactant membranes containing benzoylacetone as a mobile carrier (202)(203)(204). The same research group has reported on the effects of interfacial rate process for the extraction of hydrochloric acid by long-chain alkylamines (205).…”
Section: Kinetics In Solvent Extraction Andmentioning
confidence: 99%
“…Their prolific contributions to the subject cover the extraction kinetics of copper with benzoylacetone during drop formation (199), during drop rise (200), in a stirred transfer cell (201), and with liquid surfactant membranes containing benzoylacetone as a mobile carrier (202)(203)(204). The same research group has reported on the effects of interfacial rate process for the extraction of hydrochloric acid by long-chain alkylamines (205).…”
Section: Kinetics In Solvent Extraction Andmentioning
confidence: 99%